(3GdGbJUGO GdMVQj (B:s (3fXQjI hSjGSI (B/s - (3eMLhH, YGOd YHO GdZfjs; (3NQhaI, SgGe UOjbs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2008)
(3aj gPG GdcJGH (B: (3GdebOeI , GbJUGOjGJ GdJQcjR GdLZQGaj , GdehbY Vef GdefWbI GdMVQjI hGSJYeGdGJ GdCQV , Shb GdYed GdMVQj , GdGbJUGO GdMVQj GdMQcj , fXQjI MLe GdeOjfI haVGAGJgG , GdHjFI GdMVQjI eTcdI Gdfbd GdMVQj , GdGScGf GdMVQj , GbJUGO GdbWGY GdYGe GdMVQj , GdJNWjW GdMVQj (B.s
(3eQGLY U(B.28-53-54-111-139-162-186-243-274-303-(3bGFeI GdeUWdMGJ U(B.305-311s
Keywords: (3GdEbJUGOs; (3GdJNWjW GdEbJUGOjs; (3GdJfejI GdMVQjIs